Tribal Sub-Plan 1985-1990 Seventh Plan Tamil Nadu - Planning Commission (Planning Commission, 1985)
The Constitution of India envisages the fostering of a faster pace of development for the tribals so that they can be brought on to the sane level of development as the non-tribal groups. the directive Principles of State Policy in the Constitution, under Article 46, enjoin on the State the special responsibility of promotion, with special care, the educational and economic interest of the weaker sections of the people and, in particular, of the Scheduled Castes and Scheduled Tribes and of protecting then from social injustice and exploitation.
The Director of ADI Dravidar and Tribal Welfare, Madras